2017
DOI: 10.1016/j.jdent.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities and dental caries in six-year-old children from the Netherland s

Abstract: Our results should raise concerns about the existing social inequalities in dental caries and should encourage development of dental caries prevention strategies. New knowledge about the distribution of oral health inequalities between districts should be used to target the right audience for these strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 29 publications
11
52
0
4
Order By: Relevance
“…Moreover, during the past decade, many Swedish dental clinics have been merged into larger units for better utilization of facilities [Hassel Gustafsson and Östberg, 2017], which may prevent the targeting of individuals from underprivileged areas. In line with our results, a recent study from the Netherlands found divisions into small areas useful to target prevention efforts [van der Tas et al, 2017].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, during the past decade, many Swedish dental clinics have been merged into larger units for better utilization of facilities [Hassel Gustafsson and Östberg, 2017], which may prevent the targeting of individuals from underprivileged areas. In line with our results, a recent study from the Netherlands found divisions into small areas useful to target prevention efforts [van der Tas et al, 2017].…”
Section: Discussionsupporting
confidence: 92%
“…A Belgian study found that 5-year-old children whose mothers with higher education levels were more likely to consume less sugary drinks, brush teeth more frequently, have more dental visits, and have lower prevalence of dental caries [27]. Similar pattern has also been reported previously in a study regarding to dental caries, suggesting that mother's education level was the most important index that affect dental caries than household income and parents' occupations [13]. In line with the study conducted by Franzman et al [28] showing that daily brushing frequency of a group of American children was positively associated with both mother's and father's education levels, our findings also demonstrated that both mother's and father's education levels had significant influences on COB.…”
Section: Discussionsupporting
confidence: 71%
“…Dental caries negatively affects children's quality of life by their psychological and social relations, also causing feelings of discomfort from an early age [5,6]. Furthermore, dental caries leads to considerable cost in the short and long term [7].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a reduction in the prevalence of dental caries is desirable [8] and identifying high-risk populations for developing dental caries can help in achieving this goal by targeting the right audience with preventive strategies [7,9].…”
Section: Introductionmentioning
confidence: 99%